2020
DOI: 10.3837/tiis.2020.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analysis Approach for the Detection of High Survivable Ransomware

Abstract: Ransomware is malicious software that encrypts the user-related files and data and holds them to ransom. Such attacks have become one of the serious threats to cyberspace. The avoidance techniques that ransomware employs such as obfuscation and/or packing makes it difficult to analyze such programs statically. Although many ransomware detection studies have been conducted, they are limited to a small portion of the attack's characteristics. To this end, this paper proposed a framework for the behavioral-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…A decision tree is a straightforward structure derived from nonnodes that indicate tests across one or more characteristics and network interface layer that provide decision results. At each node of the logistic regression, the information gain measure is utilized to choose the test attribute [ 28 ]. They obtained the following metric favors characteristics with a high number of possible values.…”
Section: Attribute Extraction Methodsmentioning
confidence: 99%
“…A decision tree is a straightforward structure derived from nonnodes that indicate tests across one or more characteristics and network interface layer that provide decision results. At each node of the logistic regression, the information gain measure is utilized to choose the test attribute [ 28 ]. They obtained the following metric favors characteristics with a high number of possible values.…”
Section: Attribute Extraction Methodsmentioning
confidence: 99%
“…The features were divided into seven subset features (top20, top30, top40, top50, top60, top70, top80) by considering their importance and ranking based on phase 2 processing. The results of the experiment demonstrated that ANN showed the highest accuracy of 98.79% when the top30 of the feature set was used as training and testing [27]. However, this classification accuracy had dramatically decreased to 95.63% when the top20 of the feature set was used.…”
Section: A Behavior Basedmentioning
confidence: 99%
“…These frameworks yield promising results in detection of different types of ransomware and have potentials to be used in future research works by the cyber security community. In what follows, eight state-of-the-art frameworks including Behavior Based [27], DNAact-Ran [28], RANDS [30], RATAFIA [32], RansomWall [33], CryptoKnight [34], EldeRan [35], and DRTHIS [40] will be studied and compared.…”
Section: Ransomware Detection Frameworkmentioning
confidence: 99%
See 2 more Smart Citations